20-year follow-up of rheumatic mitral stenosis patients after percutaneous mitral commissurotomy: invasive transmitral gradient differential as a predictor of events - Ana Filipa Amador; Catarina Costa; Ricardo Pinto; Miguel Carvalho; Tânia Proença; João Calvão; Sandra Amorim; Mariana Paiva; João Carlos Silva; Rui Rodrigues (Monaldi Archives for Chest Disease, 2024)
Percutaneous mitral valve commissurotomy (PMC) is a viable alternative to mitral valve (MV) surgery in the treatment of patients with rheumatic mitral stenosis (RMS). In this single-center retrospective study of consecutive patients with RMS submitted to PMC from 1991 to 2008, we analyzed clinical, echocardiographic, and hemodynamic data and events during follow-up (FUP) until December 2021. Major adverse cardiovascular events (MACE) were a combined endpoint of all-cause death, cardiovascular hospitalization, and MV re-intervention. A total of 124 patients were enrolled: 108 (87.1%) were female, with a mean age at PMC of 46 [standard deviation (SD) 11] years. PMC was successful in 91.1%, with a mean reduction in invasive transmitral pressure gradient (TMPG) of 8 (SD 7) mmHg at PMC time. During the mean FUP of 20 (SD 6) years, 51 (41.1%) patients had MV re-intervention (86.3% surgery and 13.7% redo-PMC), 37 (29.8%) were hospitalized, and 30 (24.2%) died. Approximately 75% of patients remained MACE-free after 10 years, and this percentage decreased to around 40% after 20 years; at this time mark, about 8 in 10 patients were alive. A reduction of <5 mmHg in TMPG at PMC time was associated with a 2.7-fold greater rate of MACE compared to a reduction of ≥5 mmHg, independent of MV regurgitation after PMC and moderate disease of other valves (adjusted hazard ratio 2,7; 95% confidence interval 1.395-5.298, p=0.003). In this cohort with favorable long-term results after PMC, a reduction of <5 mmHg in TMPG at PMC time was associated with MACE during FUP. More studies are needed to validate this independent predictor.